2019
DOI: 10.3389/fneur.2019.00856
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Setting Stroke Unit in a Sub-Saharan African Public Hospital

Abstract: Introduction: Sub-Saharan Africa (SSA) has the highest stroke prevalence along with a case fatality that amounts to 40%. We aimed to assess the effect of a minimal setting stroke unit in SSA Public hospital on stroke mortality and main medical complications. Materials and Methods: The study was set in Conakry, Guinea, Ignace Deen public referral hospital. Clinical characteristics, hospital mortality and main medical stroke complications rates (pneumonia, urinary tract infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
(26 reference statements)
1
27
0
Order By: Relevance
“…The insufficient presence of oxygen and glucose for normal metabolism is the main cause of injury in stroke (30) and as the therapeutic window is limited, early recanalization has proved helpful in preventing ischemic neuronal loss (31). Thrombolytic therapies are commonly used for the treatment of ischemic stroke (32); however, the recovery of blood flow has been found to promote secondary injuries (33).…”
Section: Discussionmentioning
confidence: 99%
“…The insufficient presence of oxygen and glucose for normal metabolism is the main cause of injury in stroke (30) and as the therapeutic window is limited, early recanalization has proved helpful in preventing ischemic neuronal loss (31). Thrombolytic therapies are commonly used for the treatment of ischemic stroke (32); however, the recovery of blood flow has been found to promote secondary injuries (33).…”
Section: Discussionmentioning
confidence: 99%
“…Upon discharge, among the 349 survivors, 27.6% were independent (Rankin ≤2), 23 (6.5%) had RANKIN 0, 40 (11.4%) had RANKIN 1; 54 (15.4%) had RANKIN 3, 133 (38.2%) had RANKIN 4 and 62 (18.7%) had 5. The median RANKIN was 4 and the interquartile interval was [ [2] , [3] , [4] ].…”
Section: Resultsmentioning
confidence: 99%
“…Stroke mortality is also high in low income countries compared with those reported in western countries. Many studies have reported the in-hospital mortality of stroke in SSA with a range of 7.2%–45% [ [4] , [5] , [6] ]. We found an in-hospital case fatality of 16.8% in 85 cases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering those figures, SSA is facing a dramatic increase in stroke cases in the years to come with few healthcare means to deal with the coming epidemics, both in terms of technical facilities and in terms of trained health workers. Therefore, better understanding the specifics of stroke epidemics is needed to orient future public health policies in SSA for stroke prevention and treatment as pragmatic cost‐effective choices can impact positively stroke outcomes [5‐7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, better understanding the specifics of stroke epidemics is needed to orient future public health policies in SSA for stroke prevention and treatment as pragmatic cost-effective choices can impact positively stroke outcomes. [5][6][7] Epidemiological reports suggest that stroke in SSA is characterized by higher proportion of intra-cerebral hemorrhagic stroke (ICH) than ischemic stroke (IS). The reasons for the over-representation of ICH are unknown but are reproductible in the few epidemiological studies realized in Gambia, Cameroon, Mozambique and Kenya.…”
Section: Introductionmentioning
confidence: 99%